Pergeseran Budaya Siri’ dalam Novel Anak Dara Mulampekke Karya Mutmainnah Syam: Antropologi William A. Haviland - Talitha Cahyarani Suriyadi; Nensilianti Nensilianti; Suarni Syam Saguni (INSIGHT: Indonesian Journal Social Studies and Humanities, 2023)
Abstract.Causes of Siri' Cultural Shift in Mutmainnah Syam's Novel Anak Dara Mulampekke: Anthropology of William A. Haviland. This study aims to describe the causes of the shift in siri' culture in the novel Anak Dara Mulampekke by Mutmainnah Syam seen from the anthropological study of William A. Haviland. This research is descriptive qualitative. The research data are in the form of words, phrases, sentences and paragraphs which indicate that there is a cause for the shift in siri' culture in Mutmainnah Syam's novel Anak Dara Mulampekke. The results of this study are the causes of the shift in siri' culture which shows three descriptions, namely, the influence of foreign culture, the influence of the surrounding environment and flexibility.Keywords: Literary Anthropology, Cultural Shift, Siri'